Large-particle high-performance lithium iron manganese phosphate positive electrode material and preparation method thereof

By grinding and reacting in the ball milling tank, the iron manganese phosphate phase was generated, and the large-grained, spray-drying and sintering were performed to prepare large-grained high-performance lithium manganese phosphate positive electrode material, which solved the problems of small particles and poor conductivity of the existing materials, and achieved the high energy density and cycle stability of the materials.

CN119822344AInactive Publication Date: 2025-04-15JIANGSU HENGTRON NANOTECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411959956.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have problems such as small particles, poor conductivity, high specific surface area, poor processing performance and poor circulation performance.

Method used

By adding Li source compound, Mn source compound, Fe source compound, P source compound, doping source and carbon source to the ball milling tank, reacting while grinding to generate a lithium iron manganese phosphate phase, and undergoing multiple grinding, spray drying and sintering, large-grain high-performance lithium manganese phosphate positive electrode material is prepared.

Benefits of technology

The uniform phase structure of the material is realized, the internal resistance is reduced, the conductivity is improved, the energy density and cyclic stability of the lithium manganese iron phosphate cathode material are improved, and the processing performance and specific surface area are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822344A_ABST
    Figure CN119822344A_ABST
Patent Text Reader

Abstract

The invention discloses a large-particle high-performance lithium iron manganese phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of lithium ion battery positive electrode materials. In a traditional process, reaction phase formation usually occurs after a sintering process, while lithium manganese iron phosphate is formed through a chemical reaction before sintering, so that the uniformity of manganese iron is realized on an atomic level, the problems of large primary particle and poor electrical property of the positive electrode material lithium manganese iron phosphate are solved, and the problems of high specific surface area and poor electrical property of the lithium manganese iron phosphate are solved. The conductivity is low, the processability is poor, and the cycle performance is poor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a large-particle high-performance lithium iron manganese phosphate positive electrode material and a preparation method thereof. Background Art

[0002] The current mainstream olivine structure LiFePO4 cathode material has good cycle stability, high safety, and high discharge capacity (170mAh g -1 ), low cost, etc. However, its low discharge platform (3.4Vvs Li / Li+) and low energy density have limited its further development. LiFeMnPO4 material combines the advantages of LiFePO4 and LiMnPO4 materials. It has the same good safety as LiFePO4 and the same high energy density as LiMnPO4, and has competitive advantages and market prospects. However, LiFeMnPO4 material still has problems such as small primary particles, poor conductivity, large specific surface area, poor processing performance, and poor cycle. Summary of the invention

[0003] Based on the problems existing in the background technology, the present invention provides a large-particle high-performance lithium iron manganese phosphate positive electrode material and a preparation method thereof, which solves the problem that the primary particles of the positive electrode material lithium iron manganese phosphate are small and the electrical performance is poor, thereby solving the problems of high specific surface area, low electrical conductivity, poor processing performance, and poor cycle performance of lithium iron manganese phosphate.

[0004] The present invention is implemented by the following technical solutions:

[0005] A method for preparing a large-particle high-performance lithium manganese iron phosphate positive electrode material comprises the following steps:

[0006] (a) adding a Li source compound, a Mn source compound, an Fe source compound, a P source compound, a doping source, a carbon source and deionized water into a ball mill, adding a reaction accelerator, reacting while grinding to generate a lithium iron manganese phosphate phase, continuing to grind the lithium iron manganese phosphate phase to obtain a grinding slurry, spray drying the grinding slurry, and sintering the obtained spray-dried material once to obtain a sintered product;

[0007] (b) adding the first calcined product, a carbon source and deionized water into a ball mill, and performing mixed ball milling to obtain a second calcined slurry; spray drying the second calcined slurry for a second time, and performing a second sintering on the spray dried material to obtain a large-particle high-performance lithium manganese iron phosphate positive electrode material.

[0008] Furthermore, in step (a), the molar ratio of Li element, Mn element, Fe element, P element and doping element in the Li source compound, Mn source compound, Fe source compound, P source compound and doping source is (1.01-1.07): x:y:1:z, wherein 0.3<x<0.7, 0.3<y<0.7, x+y=0.90-0.99, 0.003<z<0.05.

[0009] Furthermore, the Li source compound in step (a) can be selected from one or more of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate;

[0010] The Mn source compound may be selected from one or more of manganese carbonate, manganese tetraoxide, manganese trioxide, manganese oxalate, manganese phosphate, ferromanganese tetraoxide, ferromanganese trioxide, ferromanganese carbonate, ferromanganese phosphate, and ferromanganese oxalate;

[0011] The Fe source compound can be selected from one or more of ferric phosphate, ferrous oxide, ferrous oxalate, ferromanganese tetroxide, ferromanganese trioxide, ferromanganese carbonate, ferromanganese phosphate, and ferromanganese oxalate;

[0012] The doping source compound may be selected from one or more of magnesium acetate, magnesium oxide, titanium dioxide, ammonium niobium oxalate, niobium pentoxide, vanadium or a vanadium compound;

[0013] The P source compound can be selected from one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, manganese phosphate, and iron phosphate.

[0014] Furthermore, the promoter in step (a) is a substance with redox properties, preferably one or more of oxalic acid, hydrogen peroxide, vitamin C, sulfur dioxide, hydrazine hydrate, and lithium borohydride.

[0015] Furthermore, the amount of the accelerator added in step (a) is 5%-50% of the total weight of the raw materials.

[0016] Furthermore, the amount of carbon source added in step (a) is 0.1%-8% of the total weight of the raw material; and during the grinding and reaction process, the solid content is 20%-45%.

[0017] Furthermore, the particle size D90 of the grinding slurry in step (a) is less than 450 nm;

[0018] The primary sintering temperature is 300-850° C., and the sintering time is 2-15 hours.

[0019] Furthermore, the amount of carbon source added in step (b) is 1%-10% of the total weight of the raw material;

[0020] During the second grinding process, the solid content is 20%-35%.

[0021] Furthermore, the particle size D50 of the second grinding slurry in step (b) is 200-400 nm;

[0022] The secondary sintering temperature is 300-850° C., and the sintering time is 2-15 hours.

[0023] Furthermore, in step (b), the average particle size of the large-particle high-performance lithium manganese iron phosphate positive electrode material is greater than 200 nm.

[0024] Beneficial effects of the present invention:

[0025] 1. In the traditional process, the reaction phase usually occurs after the sintering process, while in the present invention, lithium iron manganese phosphate is formed by chemical reaction before sintering, and the uniformity of manganese iron is achieved at the atomic level. The uniform phase structure can reduce the internal resistance, improve the conductivity of the material, and thus improve the energy density and cycle stability of the lithium iron manganese phosphate positive electrode material.

[0026] 2. The present invention performs the reaction phase formation in advance, making the reaction process more controllable and avoiding the fluctuation caused by the overly complicated or incomplete sintering process in the traditional process. This helps to improve the consistency and stability of the final product, is suitable for batch production, and ensures the controllability of product quality during large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0028] Figure 1 This is the XRD pattern of lithium manganese iron phosphate prepared in Example 1 of the present invention;

[0029] Figure 2 This is a transmission electron microscope image of lithium manganese iron phosphate prepared in Example 1 of the present invention;

[0030] Figure 3 This is a transmission electron microscope image of commercially available lithium manganese iron phosphate in comparative example 1 of the present invention;

[0031] Figure 4 This is a cycle performance diagram of lithium manganese iron phosphate prepared in Example 1 of the present invention at 45°C;

[0032] Figure 5 This is the process route of Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0034] Example 1

[0035] 29.3g Li2CO3, 27.7g manganese tetraoxide, 55.8g FePO4, 45.3g ammonium dihydrogen phosphate, 4.7g magnesium acetate, 20g hydrogen peroxide, 12g glucose, 2g PEG and 300g deionized water were placed in a ball mill, and the ball milling reaction was carried out at 800rpm for 5h. The slurry was taken out and ground to d90: about 300nm; spray drying was carried out under the conditions of peristaltic pump frequency of 40Hz, fan frequency of 65Hz, and outlet temperature of 115℃, and the obtained precursor powder was placed in a tube furnace, nitrogen was introduced into the protective atmosphere, and the temperature was increased to 500℃ at a heating rate of 10℃ / min, and then naturally cooled after 5 hours of keeping for 5 hours to obtain the precursor. 100g precursor, 8.3g glucose, 1.5g PEG and 250g deionized water were mixed and ground to d50 equal to 220nm. The mixed solution was spray dried under the conditions of a peristaltic pump frequency of 47 Hz, a fan frequency of 65 Hz and an air outlet temperature of 120°C. The spray material was placed in a tubular furnace, and a protective atmosphere of argon was introduced. The temperature was increased to 700°C at a heating rate of 10°C / min, maintained for 6 hours, and then naturally cooled to obtain the final positive electrode material.

[0036] Comparative Example 1

[0037] This comparative example is commercially available lithium manganese iron phosphate, purchased from Aladdin.

[0038] Test example

[0039] The core of the present invention is to form lithium manganese iron phosphate through chemical reaction to achieve the uniformity of manganese iron at the atomic level. The XRD pattern of the lithium manganese iron phosphate prepared in Example 1 is as follows: Figure 1 shown. Figure 2 The transmission electron microscope image shows that the lithium manganese iron phosphate formed by sintering has good sphericity and uniformity, and the average particle size is greater than 200nm.

[0040] The performance of lithium manganese iron phosphate was tested, and the test results are shown in Table 1.

[0041] Compacted conductivity test method: weigh 0.3-0.4g of the material to be tested and load it into the mold to be tested. Under a pressure of 225Mpa, the machine will measure the thickness of the compacted material and convert it into compacted density. Read the record; at 225Mpa, the impedance of the material can be read at the same time and converted into conductivity. Bet uses nitrogen as the adsorbent, weighs 0.5g of material and loads it into the sample tube. When the liquid nitrogen is kept warm, the nitrogen will be adsorbed when it flows through the material. The specific surface area is calculated based on the adsorption amount. Carbon content analysis is to load our material into a crucible, burn it in an oxygen atmosphere, and calculate the weight loss to calculate the carbon content.

[0042] For material applications, products with high compaction and high conductivity are products with excellent performance, and those with relatively lower bet will have better processability.

[0043] Table 1

[0044]

[0045]

[0046] It can be seen from the results in Table 1 that the lithium manganese iron phosphate prepared in Example 1 of the present invention has the advantages of low specific surface area, high conductivity, high compaction, etc.

[0047] Lithium manganese iron phosphate, SP, and PVDF were dispersed into battery slurry in a ratio of 90:5:5, and then coated, baked, rolled, and punched to form a battery pole piece with a diameter of 14 mm. The active material content was calculated after the pole piece was weighed. In an inert atmosphere glove box, the lithium manganese iron phosphate pole piece was assembled with a metal lithium sheet into a 2032 button half-cell, and its performance was tested. The test results are shown in Table 2.

[0048] Table 2

[0049]

[0050] Figure 4 This is a cycle performance diagram of the lithium manganese iron phosphate prepared in Example 1 of the present invention at 45°C. It can be seen from the figure that the capacity retention rate is 80% after 450 cycles; while the commercially available lithium manganese iron phosphate generally maintains 80% after 200 cycles.

[0051] Disperse lithium manganese iron phosphate, SP, and PVDF into battery slurry in a ratio of 90:5:5, weigh a certain amount of slurry and add it to the weighing bottle. The slurry level just exceeds the scale line of the rotor, and read the viscosity value at 6 rpm, 12 rpm, 30 rpm, and 60 rpm. This test item can compare the processability of the actual reaction material. The higher the value, the worse the processability.

[0052] The processing viscosity comparison is shown in Table 3, and the viscosity has been significantly improved.

[0053] Table 3

[0054] Group 6th turn 12 turns 30 rpm 60 rpm Example 1 50000 23000 12000 6000 Comparative Example 1 11000 48600 23500 15300

[0055] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a large-particle high-performance lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (a) adding a Li source compound, a Mn source compound, an Fe source compound, a P source compound, a doping source, a carbon source and deionized water into a ball mill, adding a reaction accelerator, reacting while grinding to generate a lithium iron manganese phosphate phase, continuing to grind the lithium iron manganese phosphate phase to obtain a grinding slurry, spray drying the grinding slurry, and sintering the obtained spray-dried material once to obtain a sintered product; (b) adding the first calcined product, a carbon source and deionized water into a ball mill, and performing mixed ball milling to obtain a second calcined slurry; spray drying the second calcined slurry for a second time, and performing a second sintering on the spray dried material to obtain a large-particle high-performance lithium manganese iron phosphate positive electrode material.

2. The method for preparing a large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of Li element, Mn element, Fe element, P element and doping element in the Li source compound, Mn source compound, Fe source compound, P source compound and doping source in step (a) is (1.01-1.07): x:y:1:z, wherein 0.3<x<0.7, 0.3<y<0.7, x+y=0.90-0.99, 0.003<z<0.

05.

3. The method for preparing a large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (a), the Li source compound can be selected from one or more of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate; The Mn source compound may be selected from one or more of manganese carbonate, manganese tetraoxide, manganese trioxide, manganese oxalate, manganese phosphate, ferromanganese tetraoxide, ferromanganese trioxide, ferromanganese carbonate, ferromanganese phosphate, and ferromanganese oxalate; The Fe source compound can be selected from one or more of ferric phosphate, ferrous oxide, ferrous oxalate, ferromanganese tetroxide, ferromanganese trioxide, ferromanganese carbonate, ferromanganese phosphate, and ferromanganese oxalate; The doping source compound may be selected from one or more of magnesium acetate, magnesium oxide, titanium dioxide, ammonium niobium oxalate, niobium pentoxide, vanadium or a vanadium compound; The P source compound can be selected from one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, manganese phosphate, and iron phosphate.

4. The method for preparing a large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The accelerator in step (a) is a substance with redox properties, preferably one or more of oxalic acid, hydrogen peroxide, vitamin C, sulfur dioxide, hydrazine hydrate, and lithium borohydride.

5. The method for preparing large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The amount of the accelerator added in step (a) is 5%-50% of the total weight of the material.

6. The method for preparing large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The amount of carbon source added in step (a) is 0.1%-8% of the total weight of the raw material; during the grinding and reaction process, the solid content is 20%-45%.

7. The method for preparing large-particle high-performance lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The particle size D90 of the grinding slurry in step (a) is less than 450 nm; The primary sintering temperature is 300-850° C., and the sintering time is 2-15 hours.

8. The method for preparing large-particle high-performance lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The amount of carbon source added in step (b) is 1%-10% of the total weight of the raw material; During the second grinding process, the solid content is 20%-35%.

9. The method for preparing large-particle high-performance lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The particle size D50 of the second grinding slurry in step (b) is 200-400 nm; The secondary sintering temperature is 300-850° C., and the sintering time is 2-15 hours.

10. The method for preparing large-particle high-performance lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The average particle size of the large-particle high-performance lithium manganese iron phosphate positive electrode material in step (b) is greater than 200 nm.

Citation Information

Patent Citations

  • Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof

    CN114620703A

  • Preparation method of high-capacity lithium ferric manganese phosphate material

    CN115072695A

  • Preparation method of spherical lithium manganese iron phosphate with high tap density

    CN115180608A

  • Lithium manganese iron phosphate composite material as well as preparation method and application thereof

    CN117855432A

  • Preparation method of doped lithium iron manganese phosphate positive electrode material

    CN117886289A